Steel plate
By reducing grain boundary segregation and softening the surface layer of the steel plate, the problem of hydrogen embrittlement cracking in high-strength steel plates is solved, and the hydrogen embrittlement resistance of the bending processing part is significantly improved, meeting the needs of high strength and lightweight.
Patent Information
- Application Number
- CN202380054953.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2023-04-26
- Publication Date
- 2025-03-07
AI Technical Summary
In high-strength steel plates, hydrogen embrittlement cracking is more prominent, especially in bending processing parts. While pursuing lightweighting of the vehicle body, the high-strength requirement of steel is higher, making it difficult to meet the needs of high strength and hydrogen embrittlement resistance at the same time.
By reducing the grain boundary segregation of the elements that embrittle the grain boundary, the proportion of macroscopic brittle fracture in the Chapy impact test at room temperature is controlled to be less than 35.0%, and the surface layer of the steel plate is softened. Specifically, by controlling the average Vickers hardness Hs in the area from at least one side of the steel plate to 10% of the plate thickness to be less than 0.95 times the average Vickers hardness Hc in the 1/2 position of the plate thickness to improve the hydrogen embrittlement resistance of the bending processing part.
The hydrogen embrittlement resistance characteristics of the bending part of the high-strength steel plate are significantly improved, ensuring that hydrogen embrittlement does not occur under high tensile strength conditions, and meeting the needs of lightweight and high strength while improving hydrogen embrittlement resistance.
Smart Images

Figure BDA0005249606810000341 
Figure BDA0005249606810000351 
Figure BDA0005249606810000361
Abstract
Description
Technical Field
[0001] The invention relates to a steel plate. Background Art
[0002] In recent years, the automotive industry has been seeking to reduce the weight of vehicles from the perspective of improving fuel efficiency. In order to achieve both vehicle weight reduction and collision safety, increasing the strength of the steel sheets used is an effective method, and against this background, the development of high-strength steel sheets has been promoted.
[0003] In high-strength steel sheets, hydrogen embrittlement cracking (also called delayed fracture) may become a problem. Hydrogen embrittlement cracking refers to a phenomenon in which a steel member subjected to high stress in use suddenly breaks due to hydrogen that penetrates into the steel from the environment.
[0004] In this regard, Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet having a hot-dip galvanized layer on the surface of the steel sheet, wherein the composition of the high-strength hot-dip galvanized steel sheet contains, by mass%, C: 0.08-0.35%, Si: 0.01-3.0%, Mn: 2.0-4.0%, P: 0.010% or less (excluding 0), S: 0.002% or less (excluding 0), Al: 0.01-1.50%, and B: 0.0005-0.010%, and contains Mo: 0.03-2.0%, Ti: 0.010-0.10% or less. At least one of the above, the remainder is composed of Fe and inevitable impurities; in the steel structure of the high-strength hot-dip galvanized steel sheet, in the range of 300 to 400 μm from the surface of the steel sheet along the thickness direction, the total area ratio of martensite and bainite containing carbides is 60 to 100%, the average grain size of the original austenite is 15 μm or less, and in the range of 300 to 400 μm from the surface of the steel sheet along the thickness direction, the peak height of the Auger electron spectrum of P at a position more than 5 nm away from the original austenite grain boundary relative to the peak height of the Auger electron spectrum of P in the original austenite grain boundary is 0.20 or more. In addition, Patent Document 1 also gives the following teaching: According to the above-mentioned structure, by suppressing the segregation of P to the original austenite grain boundary, a high-strength galvanized steel sheet with excellent delayed fracture resistance can be obtained.
[0005] Patent document 2 describes a high-strength hot-dip galvanized steel sheet having a hot-dip galvanized layer on the surface of the steel sheet, wherein the composition of the high-strength hot-dip galvanized steel sheet contains, by mass%, C: 0.12-0.35%, Si: 0.01-3.0%, Mn: 2.0-4.0%, P: 0.100% or less (excluding 0), S: 0.02% or less (excluding 0) and Al: 0.01-1.50%, and the remainder is composed of Fe and inevitable impurities; in the steel structure of the high-strength hot-dip galvanized steel sheet, the total of ferrite and upper bainite is 0-15%, the total of lower bainite and martensite is 80-100%, and the retained austenite is 0-10%, and the precipitate with an equivalent circle diameter of 100-2000nm is 10% in the range of 100-300μm from the surface of the steel sheet in the thickness direction. 9 ~10 12 pcs / m 2 ; The ratio of the average C content at a position 5 μm away from the surface of the steel plate along the plate thickness direction to the average C content at a position 70 μm away from the surface of the steel plate along the plate thickness direction is 0.20 to 0.80. In addition, Patent Document 2 also gives the following teaching: By making the ratio of the average C content at a position 5 μm away from the surface of the steel plate along the plate thickness direction to the average C content at a position 70 μm away from the surface of the steel plate along the plate thickness direction be 0.20 to 0.80, the stress near the surface layer can be relaxed, and excellent delayed fracture resistance characteristics can be obtained.
[0006] Patent document 3 describes an ultra-high strength cold-rolled steel sheet having excellent bendability, characterized in that it contains, by mass%, C: 0.15-0.30%, Si: 0.01-1.8%, Mn: 1.5-3.0%, P: 0.05% or less, S: 0.005% or less, Al: 0.005-0.05% and N: 0.005% or less, and the remainder is composed of Fe and unavoidable impurities, and has a Hv satisfying the following formula (1): (S) / Hv(C)≤0.8 (Hv(S): hardness of the soft part of the surface layer of the steel plate, Hv(C): hardness of the center part of the steel plate) and formula (2) 0.10≤t(S) / t≤0.30 (t(S): thickness of the soft part of the surface layer of the steel plate, t: plate thickness), and the tempered martensite in the soft part of the surface layer of the steel plate is 90% or more by volume, the structure of the center part of the steel plate is tempered martensite, and the tensile strength is 1270MPa or more. In addition, Patent Document 3 also gives the following teaching: by satisfying the above formulas (1) and (2), it has the effect of improving the bendability and delayed fracture resistance characteristics.
[0007] Patent document 4 describes a high-strength cold-rolled steel sheet, which contains, by weight, 0.05-0.20% C, 0.001-0.030% P, 0.001-0.050% S, 0.001-0.100% Al, 0.0002-0.0050% N, and one or more of 0.10-2.50% Si, 0.5-3.50% Mn, 0.10-1.5% Cr, 0.10-1.5% Mo, and 0.001-0.005% B, with the remainder being Fe and unavoidable impurities, wherein the surface layer portion, which is 0.010-0.20 mm from each side of the front and back sides of the steel sheet, is mainly composed of ferrite, and the inner layer portion is mainly composed of bainite and martensite. In addition, Patent Document 4 also provides the following teaching: According to the above-mentioned structure, since the surface layer of the steel plate has a layer mainly composed of ferrite, and the inner layer has a layer mainly composed of martensite-bainite, it is possible to provide a steel plate with excellent workability and delayed fracture resistance.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: International Publication No. 2020 / 136990
[0011] Patent Document 2: International Publication No. 2020 / 136988
[0012] Patent Document 3: Japanese Patent Application Publication No. 2011-179030
[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 10-130782 Summary of the invention
[0014] Problems to be solved by the invention
[0015] Generally speaking, it is known that hydrogen embrittlement cracking is more likely to occur as the strength of the steel increases, and is particularly likely to occur in the bending portion where large plastic strain is applied. On the other hand, in the automotive industry, etc., further weight reduction of steel is also sought, and in order to achieve such weight reduction, it is necessary to increase the strength of the steel to a level higher than before. Therefore, there is a high demand for steel that can solve the hydrogen embrittlement problem while increasing the strength to the same level or higher than before, and more specifically, for high-strength steel plates with excellent hydrogen embrittlement resistance in the bending portion.
[0016] Therefore, an object of the present invention is to provide a steel sheet having high strength and excellent hydrogen embrittlement resistance at a bent portion by a novel structure.
[0017] Means for solving problems
[0018] The present inventors have conducted studies to achieve the above-mentioned object, and as a result, have found that, for high-strength steel plates having a tensile strength of 1500 MPa or more, by simultaneously reducing the grain boundary segregation of elements that embrittle grain boundaries to control the proportion of macroscopic brittle fractures in a Charpy impact test within a prescribed range, and softening the surface layer portion of the steel plate to increase the upper limit of hydrogen amount that does not cause hydrogen embrittlement in the bent portion, i.e., the limiting hydrogen amount, the hydrogen embrittlement resistance of the bent portion can be significantly improved even in steel plates having a very high tensile strength of 1500 MPa or more, thereby completing the present invention.
[0019] The present invention which can achieve the above-mentioned object is as follows.
[0020] (1) A steel plate, characterized in that:
[0021] The chemical composition thereof is, in mass%, C: 0.15-0.40%, Si: 0.01-2.00%, Mn: 0.80-3.50%, P: 0.0001-0.0200%, S: 0.0001-0.0200%, Al: 0.001-1.000%, N: 0.0001-0.020%, O: 0.0001-0.0200%, Co: 0-0.5000%, Ni: 0-1.000%, Mo: 0-1.000%, Cr: 0-2.000%, Ti: 0-0.50 0%, B: 0 to 0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0 to 0.500%, W: 0 to 0.100%, Ta: 0 to 0.100%, Sn: 0 to 0.100%, Sb: 0 to 0.100%, As: 0 to 0.100%, Mg: 0 to 0.0500%, Ca: 0 to 0.050%, Y: 0 to 0.050%, Zr: 0 to 0.050%, La: 0 to 0.050%, Ce: 0 to 0.050%, and the remainder: Fe and impurities,
[0022] The average Vickers hardness Hs in the region from at least one surface to 10% of the plate thickness is 0.95 times or less of the average Vickers hardness Hc at a position 1 / 2 of the plate thickness,
[0023] The ratio of macroscopic brittle fractures in a Charpy impact test at room temperature is 35.0% or less, and the tensile strength is 1500 MPa or more.
[0024] (2) The steel plate according to (1) above, characterized in that:
[0025] The chemical composition contains, by mass%, one or more elements selected from the following:
[0026] Co: 0.0100~0.5000%,
[0027] Ni: 0.010~1.000%,
[0028] Mo: 0.010~1.000%,
[0029] Cr: 0.001~2.000%,
[0030] Ti: 0.001~0.500%,
[0031] B: 0.0001~0.0100%,
[0032] Nb: 0.001~0.500%,
[0033] V: 0.001~0.500%,
[0034] Cu: 0.001~0.500%,
[0035] W: 0.001~0.100%,
[0036] Ta: 0.001~0.100%,
[0037] Sn: 0.001~0.100%,
[0038] Sb: 0.001~0.100%,
[0039] As: 0.001~0.100%,
[0040] Mg: 0.0001~0.0500%,
[0041] Ca: 0.001~0.050%,
[0042] Y: 0.001~0.050%,
[0043] Zr: 0.001~0.050%,
[0044] La: 0.001 to 0.050%, and
[0045] Ce: 0.001~0.050%.
[0046] (3) The steel sheet according to (1) or (2) above, characterized in that:
[0047] The microstructure at the half thickness position contains, by area ratio:
[0048] Martensite and tempered martensite: more than 93.0% in total, and
[0049] Ferrite: less than 7.0%.
[0050] (4) The steel plate according to any one of (1) to (3) above, wherein the average carbon concentration Cs in the region from at least one surface to 10% of the plate thickness is 0.10 to 0.90 times the average carbon concentration Cc of the base material.
[0051] (5) The steel plate according to any one of (1) to (4) above, wherein the amount of P segregation in the prior austenite grain boundaries from the 1 / 8 position to the 1 / 2 position of the plate thickness is 3.50 atomic % or less.
[0052] (6) The steel sheet according to any one of (1) to (5) above, further comprising a coating layer on at least one surface, the coating layer containing at least one selected from zinc, aluminum, magnesium, and alloys thereof.
[0053] Effects of the Invention
[0054] According to the present invention, it is possible to provide a steel sheet having high strength and excellent hydrogen embrittlement resistance at a bent portion. DETAILED DESCRIPTION
[0055] An embodiment of the present invention relates to a steel plate, characterized in that:
[0056] The chemical composition is expressed in mass % by
[0057] C: 0.15~0.40%,
[0058] Si: 0.01-2.00%,
[0059] Mn: 0.80~3.50%,
[0060] P: 0.0001~0.0200%、
[0061] S: 0.0001~0.0200%,
[0062] Al: 0.001~1.000%,
[0063] N: 0.0001~0.020%,
[0064] O: 0.0001~0.0200%、
[0065] Co: 0~0.5000%,
[0066] Ni: 0~1.000%,
[0067] Mo: 0~1.000%,
[0068] Cr: 0~2.000%,
[0069] Ti: 0~0.500%,
[0070] B: 0~0.0100%,
[0071] Nb: 0~0.500%,
[0072] V: 0~0.500%、
[0073] Cu: 0~0.500%,
[0074] W: 0~0.100%、
[0075] Ta: 0~0.100%、
[0076] Sn: 0~0.100%,
[0077] Sb: 0~0.100%,
[0078] As: 0~0.100%,
[0079] Mg: 0~0.0500%,
[0080] Ca: 0~0.050%,
[0081] Y: 0~0.050%,
[0082] Zr: 0~0.050%,
[0083] La: 0~0.050%,
[0084] Ce: 0 to 0.050%, and
[0085] The rest: Fe and impurities.
[0086] The average Vickers hardness Hs in the region from at least one surface to 10% of the plate thickness is 0.95 times or less of the average Vickers hardness Hc at a position 1 / 2 of the plate thickness,
[0087] The ratio of macroscopic brittle fracture in the Charpy impact test at room temperature is 35.0% or less.
[0088] The tensile strength is above 1500MPa.
[0089] As mentioned above, it is known that hydrogen embrittlement cracking is more likely to occur as the strength of the steel material increases. In particular, in steel plates with very high strengths such as tensile strengths of more than 1500 MPa, the microstructure of the steel plate generally contains martensite as the main body in order to ensure high strength. On the other hand, in the case of such high-strength steel plates with martensite as the main body, it can be considered that hydrogen embrittlement cracking is caused by the following reasons: the hydrogen intruding into the steel is mainly concentrated in the original austenite grain boundaries in the martensite structure, which reduces the bonding strength of the grain boundaries. In this way, the grain boundaries with reduced bonding strength become the starting point of embrittlement. Generally speaking, with the increase in tensile strength, hydrogen embrittlement can occur even with a small amount of hydrogen, and the intrusion of hydrogen into steel can occur even at room temperature. Among them, there is no method to perfectly suppress the intrusion of hydrogen itself into steel or it is very difficult to perfectly suppress it. Therefore, in high-strength steel plates with tensile strengths of more than 1500 MPa, in order to completely solve the problem of hydrogen embrittlement, it becomes important to modify the structure of the bending processing part that is prone to hydrogen embrittlement due to the application of particularly large plastic strain.
[0090] Therefore, the inventors have conducted special research on improving the hydrogen embrittlement resistance of the bent portion of a steel sheet having a very high tensile strength of 1500 MPa or more. As a result, the inventors have found that it is effective to increase the upper limit of hydrogen amount that does not cause hydrogen embrittlement in the bent portion while suppressing the embrittlement of the prior austenite grain boundary that becomes the starting point of hydrogen embrittlement cracking in the microstructure. More specifically, the inventors have found that: while reducing the grain boundary segregation of elements such as P that embrittle the grain boundaries and controlling the proportion of macroscopic brittle fractures in a Charpy impact test at room temperature to less than 35.0%, in order to increase the limiting hydrogen amount in the surface portion of the steel plate that is prone to hydrogen embrittlement during bending and soften the surface portion, more specifically, by controlling the average Vickers hardness Hs in the region from the surface of at least one side of the steel plate to 10% of the plate thickness to less than 0.95 times the average Vickers hardness Hc at 1 / 2 of the plate thickness, the hydrogen embrittlement resistance of the bent portion can be significantly improved even in a steel plate with a very high tensile strength of more than 1500 MPa.
[0091] For example, the hydrogen embrittlement resistance of the bent portion can be improved by softening only the surface portion of the steel plate that is prone to hydrogen embrittlement during bending. However, in the case of a steel plate with a very high strength such as a tensile strength of 1500 MPa or more, in order to obtain sufficient hydrogen embrittlement resistance, it is necessary to greatly increase the softening degree of the surface portion. However, in such a case, although the hydrogen embrittlement resistance is improved, it becomes difficult to maintain sufficient tensile strength, i.e., a tensile strength of more than 1500 MPa. Similarly, the hydrogen embrittlement resistance can be improved by reducing the grain boundary segregation of specific elements that embrittle the grain boundaries. However, in the case of a steel plate with a very high strength such as a tensile strength of 1500 MPa or more, it is difficult to improve the hydrogen embrittlement resistance of the bent portion to the desired level only by reducing the grain boundary segregation of such specific elements. Therefore, in the steel plate involved in the embodiment of the present invention, in order to reliably maintain a tensile strength of more than 1500 MPa while achieving the desired hydrogen embrittlement resistance in the bent portion, it is very important to control the ratio of macroscopic brittle fractures in the Charpy impact test to less than 35.0% and the average Vickers hardness Hs in the area from the surface of at least one side of the steel plate to 10% of the plate thickness to less than 0.95 times the average Vickers hardness Hc at the 1 / 2 position of the plate thickness. According to the present invention, by a specific combination of these technical matters, although it is a steel plate with a very high tensile strength of more than 1500 MPa, it is possible to reliably significantly improve the hydrogen embrittlement resistance of the bent portion. Therefore, according to the present invention, even in applications such as automobiles that require contradictory characteristics such as excellent bending workability and high strength, it is possible to achieve excellent hydrogen embrittlement resistance in the bent portion while taking these characteristics into account.
[0092] Hereinafter, the steel sheet according to the embodiment of the present invention will be described in more detail. In the following description, the unit of the content of each element, i.e., "%", means "mass %" unless otherwise specified. In addition, in this specification, the numerical range represented by "to" means that the numerical values described before and after "to" are included as the lower limit and the upper limit unless otherwise specified.
[0093] [C: 0.15~0.40%]
[0094] C is an element effective for increasing tensile strength at low cost. In order to fully obtain such an effect, the C content is set to 0.15% or more. The C content may be 0.16% or more, 0.18% or more, 0.20% or more, more than 0.20%, 0.21% or more, 0.22% or more, or 0.23% or more.
[0095] On the other hand, if excessive C is contained, coarse grain boundary carbides are sometimes formed, making the grain boundary easily brittle, and microscopic cracks are introduced, so that the hydrogen embrittlement resistance is reduced and the weldability is sometimes reduced. Therefore, the C content is set to 0.40% or less. The C content may also be 0.38% or less, 0.35% or less, 0.30% or less, or 0.25% or less.
[0096] [Si: 0.01~2.00%]
[0097] Si is an element that acts as a deoxidizer and affects the morphology of carbides and retained austenite after heat treatment. If Si is not contained, it is sometimes difficult to suppress the formation of coarse oxides. The coarse oxides become the starting point of cracks, and the cracks sometimes deteriorate the hydrogen embrittlement resistance by propagating along the steel. Therefore, the Si content is set to 0.01% or more. The Si content can also be 0.05% or more, 0.10% or more, 0.30% or more, or 0.50% or more.
[0098] On the other hand, if Si is excessively contained, hydrogen embrittlement resistance may be deteriorated due to a decrease in local ductility. Therefore, the Si content is set to 2.00% or less. The Si content may also be 1.80% or less, 1.60% or less, 1.40% or less, or 1.20% or less.
[0099] [Mn: 0.80~3.50%]
[0100] Mn is an element effective in improving the hardenability of steel and increasing the strength of steel plates. In order to fully obtain such effects, the Mn content is set to 0.80% or more. The Mn content may also be 1.00% or more, 1.20% or more, 1.40% or more, or 1.60% or more.
[0101] On the other hand, if Mn is excessively contained, Mn not only promotes co-segregation with P and S, but also sometimes deteriorates corrosion resistance and hydrogen embrittlement resistance. Therefore, the Mn content is set to 3.50% or less. The Mn content may also be 3.40% or less, 3.30% or less, 3.20% or less, 3.10% or less, 3.00% or less, 2.90% or less, 2.80% or less, less than 2.60%, 2.55% or less, 2.50% or less, less than 2.50%, 2.45% or less, 2.40% or less, 2.20% or less, or 2.00% or less.
[0102] [P: 0.0001~0.0200%]
[0103] P is an element that promotes grain boundary embrittlement by segregating to the original austenite grain boundaries. If P is excessively contained, the hydrogen embrittlement resistance is significantly reduced due to grain boundary embrittlement. Therefore, the P content is set to 0.0200% or less. The P content may also be 0.0180% or less, 0.0150% or less, 0.0120% or less, or 0.0100% or less.
[0104] From the perspective of improving hydrogen embrittlement resistance, the lower the P content, the better. However, in order to reduce the P content to less than 0.0001%, refining takes a long time, resulting in a significant increase in cost. Therefore, the P content is set to 0.0001% or more. The P content can also be 0.0005% or more, 0.0010% or more, or 0.0020% or more.
[0105] [S: 0.0001~0.0200%]
[0106] S is an element that generates non-metallic inclusions such as MnS in steel. If S is excessively contained, the generation of non-metallic inclusions that become crack starting points during cold working becomes significant. In this case, cracks occur from non-metallic inclusions, and the cracks propagate through the steel material, sometimes deteriorating the hydrogen embrittlement resistance. Therefore, the S content is set to 0.0200% or less. The S content may also be 0.0180% or less, 0.0150% or less, 0.0120% or less, or 0.0100% or less.
[0107] From the perspective of improving hydrogen embrittlement resistance, the lower the S content, the better. However, in order to reduce the S content to less than 0.0001%, refining takes a long time, resulting in a significant increase in cost. Therefore, the S content is set to 0.0001% or more. The S content can also be 0.0005% or more, 0.0010% or more, or 0.0020% or more.
[0108] [Al: 0.001~1.000%]
[0109] Al is an element that acts as a deoxidizer for steel and stabilizes ferrite. In order to fully obtain such an effect, the Al content is set to 0.001% or more. The Al content may also be 0.005% or more, 0.010% or more, 0.020% or more, or 0.050% or more.
[0110] On the other hand, if Al is excessively contained, coarse Al oxides are generated, which sometimes become the starting point of cracks. In addition, the cracks propagate along the steel material, which sometimes deteriorates the hydrogen embrittlement resistance. Therefore, the Al content is set to 1.000% or less. The Al content may also be 0.950% or less, 0.900% or less, 0.800% or less, or 0.600% or less.
[0111] [N: 0.0001~0.020%]
[0112] N is an element that forms coarse nitrides in the steel sheet and reduces the hydrogen embrittlement resistance of the steel sheet. In addition, N is an element that causes pores to form during welding.
[0113] Therefore, the N content is preferably as low as possible, and is set to 0.020% or less. The N content may be 0.018% or less, 0.016% or less, 0.012% or less, or 0.010% or less.
[0114] On the other hand, reducing N to less than 0.0001% leads to a significant increase in manufacturing cost. Therefore, the N content is set to 0.0001% or more. The N content may be 0.0005% or more, 0.001% or more, or 0.002% or more.
[0115] [O: 0.0001~0.0200%]
[0116] O is an element that forms oxides and deteriorates the hydrogen embrittlement resistance. In particular, oxides are mostly present as inclusions. If present in the punched end face or the cut surface, notch-shaped damage and coarse dimples are formed on the end face, thus causing stress concentration during strong processing, becoming the starting point for the formation of cracks, and sometimes leading to a significant deterioration in processability. If O is excessively contained, the tendency for the hydrogen embrittlement resistance and processability to deteriorate becomes significant. Therefore, the O content is set to 0.0200% or less. The O content may also be 0.0180% or less, 0.0150% or less, 0.0120% or less, or 0.0100% or less.
[0117] The lower the O content, the better. However, reducing the O content to less than 0.0001% leads to a significant increase in manufacturing costs. Therefore, the O content is set to 0.0001% or more. The O content may also be 0.0005% or more, 0.0010% or more, or 0.0015% or more.
[0118] The basic chemical composition of the steel sheet according to the embodiment of the present invention is as described above. In addition, the steel sheet may also contain at least one of the following arbitrarily selected elements instead of a part of the iron in the remaining part as needed. For example, the steel sheet may also contain at least one selected from Co: 0 to 0.5000%, Ni: 0 to 1.000%, Mo: 0 to 1.000%, Cr: 0 to 2.000%, Ti: 0 to 0.500%, B: 0 to 0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0 to 0.500%, W: 0 to 0.100% and Ta: 0 to 0.100%. In addition, the steel sheet may also contain at least one selected from Sn: 0 to 0.100%, Sb: 0 to 0.100% and As: 0 to 0.100%. Furthermore, the steel plate may contain at least one selected from the group consisting of Mg: 0 to 0.0500%, Ca: 0 to 0.050%, Y: 0 to 0.050%, Zr: 0 to 0.050%, La: 0 to 0.050%, and Ce: 0 to 0.050%. These arbitrarily selected elements will be described in detail below.
[0119] [Co: 0~0.5000%]
[0120] Co is an element effective in controlling the carbide morphology and increasing the strength of the steel sheet. The Co content may be 0%, but in order to obtain these effects, the Co content is preferably 0.0010% or more. The Co content may also be 0.0100% or more, 0.0200% or more, 0.0500% or more, or 0.1000% or more.
[0121] On the other hand, if Co is excessively contained, coarse Co carbides precipitate, and hydrogen embrittlement resistance may be deteriorated. Therefore, the Co content is set to 0.5000% or less. The Co content may be 0.4000% or less, 0.3000% or less, or 0.2000% or less.
[0122] [Ni: 0~1.000%]
[0123] Ni is an element effective in improving the strength of steel sheets. In addition, Ni is also an element effective in improving wettability and promoting alloying reactions. The Ni content may be 0%, but in order to obtain these effects, the Ni content is preferably 0.001% or more. The Ni content may also be 0.010% or more, 0.020% or more, 0.050% or more, or 0.100% or more.
[0124] On the other hand, if Ni is excessively contained, hydrogen embrittlement resistance may be reduced. Therefore, the Ni content is set to 1.000% or less. The Ni content may be 0.900% or less, 0.800% or less, 0.600% or less, or 0.300% or less.
[0125] [Mo: 0~1.000%]
[0126] Mo is an element effective in improving the strength of steel sheets. In addition, Mo is an element that has an inhibitory effect on the ferrite transformation that occurs when heat treatment is performed using a continuous annealing device or a continuous hot-dip galvanizing device. The Mo content may be 0%, but in order to obtain these effects, the Mo content is preferably 0.001% or more. The Mo content may also be 0.010% or more, 0.020% or more, 0.050% or more, or 0.080% or more.
[0127] On the other hand, even if Mo is excessively contained, the effect of suppressing ferrite transformation is saturated, or hydrogen embrittlement resistance is sometimes reduced due to the formation of coarse intermetallic compounds and carbides. Therefore, the Mo content is set to 1.000% or less. The Mo content may also be 0.900% or less, 0.800% or less, 0.600% or less, or 0.300% or less.
[0128] [Cr: 0~2.000%]
[0129] Cr is an element that suppresses pearlite transformation and is effective for increasing the strength of steel. The Cr content may be 0%, but in order to obtain such an effect, the Cr content is preferably 0.001% or more. The Cr content may also be 0.005% or more, 0.010% or more, 0.020% or more, or 0.050% or more.
[0130] On the other hand, if Cr is excessively contained, coarse Cr carbides are formed in the central segregation portion, and hydrogen embrittlement resistance may be reduced. Therefore, the Cr content is set to 2.000% or less. The Cr content may also be 1.800% or less, 1.500% or less, 1.000% or less, or 0.500% or less.
[0131] [Ti: 0~0.500%]
[0132] Ti is an element that contributes to improving the strength of the steel sheet through precipitate strengthening, fine grain strengthening by suppressing ferrite grain growth, and dislocation strengthening by suppressing recrystallization. The Ti content may be 0%, but in order to obtain these effects, the Ti content is preferably 0.001% or more. The Ti content may also be 0.005% or more, 0.010% or more, or 0.050% or more.
[0133] On the other hand, if Ti is excessively contained, precipitation of carbonitrides increases, and hydrogen embrittlement resistance may deteriorate. Therefore, the Ti content is set to 0.500% or less. The Ti content may also be 0.450% or less, 0.400% or less, 0.300% or less, or 0.100% or less.
[0134] [B: 0~0.0100%]
[0135] B is an element that inhibits the formation of ferrite and pearlite during cooling from the austenite temperature range and promotes the formation of low-temperature transformation structures such as bainite or martensite. In addition, B is an element that is beneficial to the high strength of steel. The B content may be 0%, but in order to obtain these effects, the B content is preferably 0.0001% or more. The B content may also be 0.0003% or more, 0.0005% or more, or 0.0010% or more.
[0136] On the other hand, if B is excessively contained, coarse B oxides are sometimes generated in the steel. This oxide becomes the starting point for the formation of voids during cold working, so coarse B oxides are generated and the hydrogen embrittlement resistance is sometimes deteriorated. Therefore, the B content is set to 0.0100% or less. The B content may also be 0.0080% or less, 0.0060% or less, 0.0050% or less, or 0.0020% or less.
[0137] [Nb: 0~0.500%]
[0138] Nb is an element effective in controlling the morphology of carbides and is also an element effective in improving toughness by refining the structure. The Nb content may be 0%, but in order to obtain these effects, the Nb content is preferably 0.001% or more. The Nb content may also be 0.002% or more, 0.010% or more, or 0.020% or more.
[0139] On the other hand, if Nb is excessively contained, coarse Nb carbides are sometimes generated. The coarse Nb carbides are prone to cracking, and sometimes deteriorate the hydrogen embrittlement resistance. Therefore, the Nb content is set to 0.500% or less. The Nb content may also be 0.450% or less, 0.400% or less, 0.300% or less, or 0.100% or less.
[0140] [V: 0~0.500%]
[0141] V is an element that contributes to improving the strength of the steel sheet through precipitate strengthening, fine grain strengthening by suppressing ferrite grain growth, and dislocation strengthening by suppressing recrystallization. The V content may be 0%, but in order to obtain these effects, the V content is preferably 0.001% or more. The V content may also be 0.002% or more, 0.010% or more, or 0.020% or more.
[0142] On the other hand, if V is excessively contained, precipitation of carbonitrides increases, and hydrogen embrittlement resistance may deteriorate. Therefore, the V content is set to 0.500% or less. The V content may also be 0.450% or less, 0.400% or less, 0.300% or less, or 0.100% or less.
[0143] [Cu: 0~0.500%]
[0144] Cu is an element effective in improving the strength of steel sheets. The Cu content may be 0%, but in order to obtain such an effect, the Cu content is preferably 0.001% or more. The Cu content may also be 0.002% or more, 0.010% or more, or 0.030% or more.
[0145] On the other hand, if Cu is excessively contained, hydrogen embrittlement resistance may deteriorate. In addition, if the Cu content is high, the steel material may become brittle during hot rolling, and hot rolling may become difficult. Therefore, the Cu content is set to 0.500% or less. The Cu content may also be 0.450% or less, 0.400% or less, 0.300% or less, or 0.100% or less.
[0146] [W: 0~0.100%]
[0147] W is an element effective in improving the strength of steel sheets. In addition, W forms precipitates and crystals. Since precipitates and crystals containing W become hydrogen trapping sites, W is an element effective in improving hydrogen embrittlement resistance. The W content may be 0%, but in order to obtain these effects, the W content is preferably 0.001% or more. The W content may also be 0.002% or more, 0.005% or more, or 0.010% or more.
[0148] On the other hand, if W is excessively contained, coarse W precipitates or crystals are sometimes generated. The coarse W precipitates or crystals are prone to cracking, and sometimes the cracks propagate along the steel under relatively low load stress. Therefore, if coarse W precipitates or crystals are generated, the hydrogen embrittlement resistance is sometimes deteriorated. Therefore, the W content is set to 0.100% or less. The W content may also be 0.080% or less, 0.060% or less, 0.050% or less, or 0.030% or less.
[0149] [Ta: 0~0.100%]
[0150] Ta is an element effective in controlling the carbide morphology and increasing the strength of the steel sheet. The Ta content may be 0%, but in order to obtain these effects, the Ta content is preferably 0.001% or more. The Ta content may also be 0.002% or more, 0.005% or more, or 0.010% or more.
[0151] On the other hand, if Ta is excessively contained, a large amount of fine Ta carbides will precipitate, which may cause a decrease in ductility or a decrease in bending resistance and hydrogen embrittlement resistance with an increase in steel sheet strength. Therefore, the Ta content is set to 0.100% or less. The Ta content may also be 0.080% or less, 0.060% or less, 0.050% or less, or 0.020% or less.
[0152] [Sn: 0~0.100%]
[0153] Sn is an element contained in steel when scrap is used as a steel raw material. If the Sn content is high, the hydrogen embrittlement resistance may be reduced due to grain boundary embrittlement. Therefore, the Sn content is set to 0.100% or less. The Sn content may also be 0.060% or less, 0.030% or less, or 0.020% or less.
[0154] The lower the Sn content, the better. It can be 0%, but it takes a long time to reduce the Sn content to less than 0.001%, which leads to a significant increase in cost. Therefore, the Sn content can be 0.001% or more. The Sn content can also be 0.002% or more, 0.005% or more, or 0.010% or more.
[0155] [Sb: 0~0.100%]
[0156] Sb, like Sn, is an element contained when scrap is used as a steel raw material. In addition, Sb is an element that significantly segregates to grain boundaries, causing grain boundary embrittlement and reduced ductility. Therefore, the Sb content is set to 0.100% or less. The Sb content may also be 0.040% or less, 0.030% or less, or 0.020% or less.
[0157] The lower the Sb content, the better. It can be 0%, but it takes a long time to reduce the Sb content to less than 0.001%, which leads to a significant increase in cost. Therefore, the Sb content can be 0.001% or more. The Sb content can also be 0.002% or more, 0.005% or more, or 0.008% or more.
[0158] [As: 0~0.100%]
[0159] As, like Sn and Sb, is an element contained when scrap is used as a steel raw material. In addition, As is an element that significantly segregates to grain boundaries, causing grain boundary embrittlement and reduced ductility. Therefore, the As content is set to 0.100% or less. The As content may also be 0.040% or less, 0.030% or less, or 0.020% or less.
[0160] The lower the As content, the better. It can be 0%, but it takes a long time to reduce the As content to less than 0.001%, which leads to a significant increase in cost. Therefore, the As content can be 0.001% or more. The As content can also be 0.002% or more, 0.003% or more, or 0.005% or more.
[0161] [Mg: 0~0.0500%]
[0162] Mg is an element that can control the sulfide form by containing a trace amount. The Mg content may be 0%, but in order to obtain such an effect, the Mg content is preferably 0.0001% or more. The Mg content may also be 0.0005% or more, 0.0010% or more, 0.0015% or more, or 0.0020% or more.
[0163] On the other hand, if Mg is excessively contained, coarse inclusions are formed, and hydrogen embrittlement resistance may be reduced. Therefore, the Mg content is set to 0.0500% or less. The Mg content may also be 0.0300% or less, 0.0100% or less, 0.0050% or less, or 0.0030% or less.
[0164] [Ca: 0~0.050%]
[0165] Ca is useful as a deoxidizing element and is also an element that has an effect on controlling the sulfide morphology. The Ca content may be 0%, but in order to obtain these effects, it is preferably set to 0.0001% or more. The Ca content may also be 0.0005% or more, 0.001% or more, or 0.002% or more.
[0166] On the other hand, if Ca is excessively contained, coarse inclusions are formed, and hydrogen embrittlement resistance may be reduced. Therefore, the Ca content is set to 0.050% or less. The Ca content may also be 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.
[0167] [Y: 0~0.050%]
[0168] Y is an element that can control the sulfide form by containing a trace amount, similarly to Mg. The Y content may be 0%, but in order to obtain such an effect, the Y content is preferably 0.0001% or more. The Y content may also be 0.0005% or more, 0.001% or more, or 0.002% or more.
[0169] On the other hand, if Y is excessively contained, coarse Y oxides are generated, and hydrogen embrittlement resistance may be reduced. Therefore, the Y content is set to 0.050% or less. The Y content may also be 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.
[0170] [Zr: 0~0.050%]
[0171] Zr, like Mg, is an element that can control the sulfide form by containing a trace amount. The Zr content may be 0%, but in order to obtain such an effect, the Zr content is preferably 0.0001% or more. The Zr content may also be 0.0005% or more, 0.001% or more, or 0.002% or more.
[0172] On the other hand, if Zr is excessively contained, coarse Zr oxides are generated, and hydrogen embrittlement resistance may be reduced. Therefore, the Zr content is set to 0.050% or less. The Zr content may also be 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.
[0173] [La: 0~0.050%]
[0174] La, like Mg, is an element that can control the sulfide form by containing a trace amount. The La content may be 0%, but in order to obtain such an effect, the La content is preferably 0.0001% or more. The La content may also be 0.0005% or more, 0.001% or more, or 0.002% or more.
[0175] On the other hand, if La is excessively contained, La oxides are generated, and hydrogen embrittlement resistance may be reduced. Therefore, the La content is set to 0.050% or less. The La content may also be 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.
[0176] [Ce: 0~0.050%]
[0177] Ce, like Mg, is an element that can control the sulfide form by containing a trace amount. The Ce content may be 0%, but in order to obtain such an effect, the Ce content is preferably 0.0001% or more. The Ce content may also be 0.0005% or more, 0.001% or more, or 0.002% or more.
[0178] On the other hand, if Ce is excessively contained, Ce oxides are generated, and hydrogen embrittlement resistance may be reduced. Therefore, the Ce content is set to 0.050% or less. The Ce content may also be 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.
[0179] In the steel sheet according to the embodiment of the present invention, the remainder other than the above elements is composed of Fe and impurities. Impurities are components mixed into raw materials such as ore and waste materials for various reasons during the industrial production of steel sheets.
[0180] The chemical composition of the steel plate involved in the embodiment of the present invention can be measured by ordinary analytical methods. For example, it is sufficient to measure the cuttings by ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) according to JIS G1201: 2014. Specifically, for example, it can be specified by collecting a 35 mm square test piece from the steel plate, grinding the test piece to 1 / 2 of the plate thickness, and measuring the ground surface according to the conditions based on a pre-made calibration curve using ICPS-8100 (measuring device) manufactured by Shimadzu Corporation. C and S that cannot be measured by ICP-AES can be measured by the combustion-infrared absorption method, N can be measured by the inert gas melting-thermal conductivity method, and O can be measured by the inert gas melting-non-dispersive infrared absorption method. When the steel plate surface has a coating layer, the chemical composition analysis can be performed after the coating layer is removed by mechanical grinding.
[0181] [Preferred Microstructure of Steel Plate]
[0182] The microstructure of the steel plate involved in the embodiment of the present invention may be any microstructure that satisfies the main condition of a tensile strength of 1500 MPa or more. More specifically, the present invention aims to provide a high-strength steel plate having excellent hydrogen embrittlement resistance in a bent portion as described above. For a high-strength steel plate having a tensile strength of 1500 MPa or more, the purpose is achieved by controlling the ratio of macroscopic brittle fractures in a Charpy impact test at room temperature to less than 35.0%, and controlling the average Vickers hardness Hs in the region from the surface of at least one side of the steel plate to 10% of the plate thickness to less than 0.95 times the average Vickers hardness Hc at the 1 / 2 position of the plate thickness. Therefore, it is obvious that the microstructure of the steel plate is not an essential technical feature in achieving the purpose of the present invention. The preferred microstructure of the steel plate having a tensile strength of 1500 MPa or more involved in the embodiment of the present invention is described in detail below, but these descriptions are intended only to exemplify a steel plate having a tensile strength of 1500 MPa or more, and are not intended to limit the present invention to a steel plate having such a specific microstructure. In addition, in the steel plate according to the embodiment of the present invention, as described above, since the surface layer of the steel plate is softened, the microstructures of the surface layer and the inner layer of the steel plate are sometimes different. Therefore, the microstructure at the position of 1 / 2 of the plate thickness is specified below by taking the part of the steel plate that is not softened as a representative.
[0183] [Martensite and tempered martensite: more than 93.0% in total]
[0184] The microstructure at the 1 / 2 position of the plate thickness of the steel plate is not particularly limited, but it is preferred that the total area ratio of martensite and tempered martensite exceeds 93.0%. By containing the prescribed chemical composition described above, in particular, by having a C content of 0.15% or more and containing more than 93.0% of martensite and tempered martensite at the 1 / 2 position of the plate thickness by area ratio, a tensile strength of more than 1500 MPa can be achieved. The total area ratio of martensite and tempered martensite may also be more than 95.0% or more than 97.0%. The upper limit of the total area ratio of martensite and tempered martensite is not particularly limited and may also be 100%. For example, the area ratio of martensite and tempered martensite may also be less than 99.0% or less than 98.0%.
[0185] [Ferrite: less than 7.0%]
[0186] The microstructure at the 1 / 2 position of the plate thickness of the steel plate is not particularly limited, but it is preferable to contain ferrite at an area ratio of less than 7.0%. Since ferrite is a soft structure, by limiting the area ratio of ferrite to less than 7.0% relative to the area ratio of the above-mentioned martensite and tempered martensite exceeding 93.0%, a tensile strength of more than 1500 MPa can be achieved. The area ratio of ferrite can also be less than 5.0% or less than 3.0%, for example, it can also be 0%. On the other hand, as mentioned above, ferrite is easy to deform because it is a soft structure, which helps to improve the ductility of the steel plate. Therefore, from the viewpoint of improving the ductility of the steel plate, the area ratio of ferrite can also be more than 1.0% or more than 2.0%.
[0187] [Remaining structure: at least one of bainite, pearlite and retained austenite]
[0188] The remaining structure other than martensite, tempered martensite and ferrite may also be 0% in terms of area ratio, but in the case of the remaining structure, it is preferred that the remaining structure be at least one of bainite, pearlite and retained austenite. The area ratio of the remaining structure is not particularly limited, and may be, for example, 0% or more and less than 7.0%, 0 to 5.0%, or 0 to 3.0%. On the other hand, to make the area ratio of the remaining structure 0%, strict control is required during the manufacturing process of the steel plate, which sometimes results in a decrease in the yield. Therefore, the area ratio of the remaining structure may also be 1.0% or more.
[0189] [Identification and calculation of microstructure]
[0190] [Martensite and tempered martensite]
[0191] The identification and calculation of the microstructure at the 1 / 2 position of the steel plate thickness can be carried out by the following method. First, a sample having a thickness section parallel to the rolling direction of the steel plate is collected, and the section is used as the observation surface. The observation surface is corroded with nitric acid, and in the corroded observation surface, a 100μm×100μm area centered on the 1 / 2 position of the plate thickness from the surface of the steel plate is used as the observation area. The observation area is observed at 1000 to 50000 times by electron channel contrast imaging using a field emission scanning electron microscope (FE-SEM). Electron channel contrast imaging is a method of detecting the crystal orientation difference within the grain as the difference in contrast of the image. For martensite and tempered martensite, the total area ratio can be calculated from the image taken through the electron channel contrast. These structures are more difficult to corrode than ferrite, so they exist as convex parts on the structure observation surface. Tempered martensite is an aggregation of lath-shaped grains, and contains iron-based carbides with a long diameter of 20 nm or more. The carbides belong to multiple variants, that is, multiple iron-based carbide groups extending in different directions. In addition, retained austenite also exists as convex parts on the microstructure observation surface. Therefore, by subtracting the area ratio of retained austenite measured by the steps described below from the area ratio of the convex parts obtained by the above steps, the total area ratio of martensite and tempered martensite can be accurately determined.
[0192] [Ferrite]
[0193] The area ratio of ferrite can be obtained by observing the 100μm×100μm area centered at 1 / 2 of the thickness of the steel plate surface through the above-mentioned electron channel contrast imaging. The area that can be identified as a contrast of uniform intermediate brightness (gray) in electron channel contrast imaging is polygonal ferrite, and it is judged to be ferrite. Such brightness judgment is a degree of judgment that can be implemented as a normal structural observation by any technician in this field. Furthermore, the area identified as the contrast of uniform intermediate brightness is an area that is easily corroded by corrosion and becomes a concave portion in the surface morphology. For the 8 fields of view in the 35μm×25μm electron channel contrast imaging, the area ratio of polygonal ferrite in each field of view is calculated by the image analysis method, and their average value is taken as the area ratio of ferrite.
[0194] [Bainite, pearlite and retained austenite]
[0195] The area ratio of retained austenite can be calculated by X-ray measurement. First, mechanical grinding and chemical grinding are used to remove the sample from the plate surface to 1 / 2 of the plate thickness in the plate thickness direction. Then, for the ground sample, MoKα rays are used as characteristic X-rays, and the structural fraction of retained austenite is calculated from the integrated intensity ratio of the diffraction peaks of the bcc phase (200), (211) and the fcc phase (200), (220), (311) obtained, and it is used as the area ratio of retained austenite. In addition, the area ratio of pearlite and bainite can also be calculated from the image taken by the above-mentioned electron channel contrast. Pearlite is a structure composed of plate-like carbides and ferrite. In addition, bainite is an aggregation of lath-shaped grains, which does not contain iron-based carbides with a long diameter of more than 20nm, or belongs to a group of iron-based carbides with a long diameter of more than 20nm, and the carbides are a single variant, that is, they are elongated in the same direction. Here, the iron-based carbide group extending in the same direction means that the difference in the extending directions of the iron-based carbide group is within 5°.
[0196] [Hs / Hc≤0.95]
[0197] In an embodiment of the present invention, the average Vickers hardness Hs in the region from the surface of at least one side of the steel plate (when there is a coating layer such as a plating layer on the surface of the steel plate, from the interface between the coating layer and the steel plate) to 10% of the plate thickness is less than 0.95 times the average Vickers hardness Hc at 1 / 2 of the plate thickness. Generally speaking, for high-strength steel plates above 1500 MPa, sufficient bending workability is sometimes not obtained, and there is a problem that hydrogen embrittlement is easily generated due to the relatively large plastic strain given to the bent portion. However, according to an embodiment of the present invention, by controlling the average Vickers hardness Hs in the region from the surface of at least one side of the steel plate, preferably from the surfaces of both sides to 10% of the plate thickness to be less than 0.95 times the average Vickers hardness Hc at 1 / 2 of the plate thickness, the surface layer of the steel plate is softened, and the bending workability can be significantly improved while increasing the upper limit of hydrogen amount, i.e., the limiting hydrogen amount, which does not cause hydrogen embrittlement in the bent portion. In addition, as described above, although it is preferred that Hs / Hc≤0.95 is satisfied on both surfaces of the steel plate, the embodiment in which Hs / Hc≤0.95 is satisfied only on at least one surface of the steel plate is of course also included in the present invention. This is because: as long as Hs / Hc≤0.95 is satisfied on any one surface, compared with the case where Hs / Hc≤0.95 is not satisfied on both surfaces, the bending workability can be significantly improved while the limit hydrogen amount in the bending portion is increased. Therefore, by combining with the control of the ratio of macroscopic brittle fractures described in detail later, the hydrogen embrittlement resistance of the bending portion can be significantly improved even in steel plates with very high tensile strengths of more than 1500 MPa. From the viewpoint of improving these effects, Hs is preferably a smaller value relative to Hc. For example, Hs may be 0.92 times or less, 0.90 times or less, 0.88 times or less, 0.85 times or less, 0.82 times or less, 0.80 times or less, 0.78 times or less, 0.75 times or less, or 0.70 times or less of Hc. On the other hand, the lower limit is not particularly limited, and any appropriate value can be selected. For example, Hs may be 0.20 times or more or 0.30 times or more of Hc, but from the viewpoint of ensuring higher strength of the steel plate, Hs may be 0.40 times or more, 0.45 times or more, or 0.50 times or more of Hc, for example.
[0198] [Determination of Hs and Hc]
[0199] In the present invention, the "average Vickers hardness Hs in the area from the surface to 10% of the plate thickness" and the "average Vickers hardness Hc in the position of 1 / 2 of the plate thickness" can be determined by the following method. The Vickers hardness test can be performed in accordance with JIS Z2244-1:2020. First, a test piece is cut from any position more than 50 mm from the end of the steel plate in such a way that a section perpendicular to the surface (plate thickness section) can be observed. From a depth position of 2 μm from the surface of the test piece (when there is a coating layer such as a plating layer on the surface of the test piece, from the interface between the coating layer and the base material) to a depth position of 1 / 10 of the plate thickness, it is divided into nine equal parts to obtain 10 depth positions, and the Vickers hardness at the 10 depth positions is measured with a 10g indentation load, and their average value is determined as the average Vickers hardness Hs in the area from the surface to 10% of the plate thickness. Next, the Vickers hardness at the 1 / 2 position of the plate thickness of the test piece is measured with a 10g indentation load, and then from this position, in a direction perpendicular to the plate thickness direction and parallel to the rolling direction, the Vickers hardness of a total of 5 points or more, for example 10 points, is measured with a 10g indentation load, and their average value is determined as the average Vickers hardness Hc at the 1 / 2 position of the plate thickness. It is preferred to set the interval between each measurement point at the 1 / 2 position of the plate thickness to a distance of more than 4 times the indentation. The so-called distance of more than 4 times the indentation refers to a distance of more than 4 times the length of the diagonal line in the rectangular opening of the indentation produced by the diamond indenter when measuring the Vickers hardness. The value of Hs / Hc can be determined based on the Hs and Hc obtained in this way. In the case where the surface layer portions on both sides of the steel plate are softened, the average Vickers hardness Hs in the area from the surface of the other side to 10% of the plate thickness can be determined by measuring in the same manner as described above.
[0200] [0.10≤Cs / Cc≤0.90]
[0201] In an embodiment of the present invention, the average carbon concentration Cs in the region from the surface of at least one side of the steel plate (when there is a coating layer such as a plating layer on the surface of the steel plate, from the interface between the coating layer and the steel plate) to 10% of the plate thickness is preferably 0.10 to 0.90 times the average carbon concentration Cc of the base material. By controlling the average carbon concentration Cs in the region from the surface of at least one side of the steel plate to 10% of the plate thickness to be less than 0.90 times the average carbon concentration Cc of the base material, the average Vickers hardness Hs in the region from the surface of at least one side of the steel plate to 10% of the plate thickness can be reliably controlled to be less than 0.95 times the average Vickers hardness Hc in the 1 / 2 position of the plate thickness. Therefore, in addition to improving the hydrogen embrittlement resistance, it is also very effective in improving the bending workability. In addition, although it is preferred to control the Cs of the surfaces of both sides of the steel plate to be less than 0.90 times the average carbon concentration Cc of the base material, that is, to satisfy Cs / Cc≤0.90 on the surfaces of both sides of the steel plate, the embodiment in which Cs / Cc≤0.90 is satisfied only on the surface of at least one side of the steel plate is of course also included in the present invention. This is because: as long as Cs / Cc≤0.90 is satisfied on the surface of any one side, a sufficient effect can be achieved compared to the case where Cs / Cc≤0.90 is not satisfied on the surfaces of both sides. From the viewpoint of further improving these effects, it is preferred that Cs is a smaller value relative to Cc. For example, Cs may be less than 0.85 times, less than 0.80 times, less than 0.75 times, less than 0.70 times, less than 0.65 times, less than 0.60 times, or less than 0.55 times of Cc. On the other hand, from the viewpoint of ensuring higher strength of the steel sheet, Cs is preferably 0.10 times or more of Cc, for example, 0.15 times or more, 0.20 times or more, 0.25 times or more, 0.30 times or more, 0.35 times or more, or 0.40 times or more.
[0202] [Determination of Cs and Cc]
[0203] In the present invention, "the average carbon concentration Cs in the area from the surface to 10% of the plate thickness" and "the average carbon concentration Cc of the base material" can be determined by a high-frequency glow discharge spectrometer (GDS) as follows. Specifically, the following method can be used: the surface of the steel plate is placed in an Ar atmosphere, glow plasma is generated by applying a voltage, and in this state, the surface of the steel plate is sputtered while analyzing in the depth direction. Then, the elements contained in the material are identified from the wavelength of the element-specific luminescence spectrum emitted by excited atoms in the glow plasma, and the luminescence intensity of the identified elements is evaluated. The data in the depth direction can be evaluated from the sputtering time. Specifically, by using a standard sample in advance to determine the relationship between the sputtering time and the sputtering depth, the sputtering time can be converted into the sputtering depth. Therefore, the sputtering depth converted from the sputtering time can be defined as the depth from the material surface. The obtained luminescence intensity can be converted into mass % by making a calibration curve. The average carbon concentration in the area from the surface measured in this way (when there is a coating layer such as a plating layer on the surface of the steel plate, from the interface between the coating layer and the steel plate) to 0.1 to 10% of the plate thickness is determined as Cs. On the other hand, the average value of the luminescence intensity of carbon is calculated according to the depth range where its luminescence intensity is very stable. For example, the average value of the luminescence intensity of C in the area from the surface of the steel plate to 15 to 25% of the plate thickness is calculated, and this value is determined as the average carbon concentration Cc of the base material. The value of Cs / Cc is determined based on the Cs and Cc obtained in this way. When the surface layer portions on both sides of the steel plate are softened, the average carbon concentration Cs in the area from the surface of the other side to 10% of the plate thickness can be determined by measuring in the same way as described above.
[0204] The control of 0.10≤Cs / Cc≤0.90 based on decarburization shown above is only one preferred means for achieving the desired softening in the surface portion of the steel plate, i.e., Hs / Hc≤0.95. In other words, the feature of Hs / Hc≤0.95 involved in the embodiment of the present invention can be achieved by any appropriate means known to those skilled in the art. For example, the feature of Hs / Hc≤0.95 can also be achieved by modifying the structure in the surface portion of the steel plate into a coarser structure than the inside of the steel plate by performing appropriate heat treatment, thereby softening the surface portion. Alternatively, the feature of Hs / Hc≤0.95 can also be achieved by constituting the structure in the surface portion of the steel plate with a softer structure than the inside of the steel plate.
[0205] [Ratio of macroscopic brittle fracture in Charpy impact test at room temperature: 35.0% or less]
[0206] In the steel plate according to the embodiment of the present invention, the ratio of macroscopic brittle fractures in the Charpy impact test at room temperature (about 25°C) is 35.0% or less. In the present invention, the ratio of macroscopic brittle fractures refers to the ratio of brittle fractures in the base material portion where the softened portion of the surface layer of the steel plate is removed. The inventors have found that the ratio of macroscopic brittle fractures in the Charpy impact test at room temperature is closely related to the embrittlement of the prior austenite grain boundary that becomes the starting point of hydrogen embrittlement cracking in the microstructure, and that the hydrogen embrittlement resistance of the steel plate can be improved if the resistance to embrittlement of the base material portion is high. Specifically, by limiting the ratio of such macroscopic brittle fractures in the Charpy impact test at room temperature to 35.0% or less, the hydrogen embrittlement resistance of the steel plate can be reliably improved, and by combining with the prescribed softening in the surface layer portion of the steel plate described above, the hydrogen embrittlement resistance of the bent portion can be significantly improved even in a steel plate having a very high tensile strength of 1500 MPa or more. From the viewpoint of improving hydrogen embrittlement resistance, the smaller the proportion of macroscopic brittle fractures in the Charpy impact test at room temperature, the more preferred, for example, it may be less than 30.0%, less than 25.0%, less than 20.0% or less than 15.0%. On the other hand, the lower limit is not particularly limited and may be 0%. For example, the proportion of macroscopic brittle fractures in the Charpy impact test at room temperature may be more than 0.1%, more than 0.2%, more than 0.4%, more than 0.6%, more than 0.8%, more than 1.0%, more than 3.0% or more than 5.0%.
[0207] [Determination of the ratio of macroscopic brittle fracture]
[0208] In the present invention, the proportion of macroscopic brittle fractures in the Charpy impact test at room temperature can be determined as follows. First, a V-notch test piece of 55 mm in length, 10 mm in width and the specified steel plate thickness specified in JIS Z2242:2018 is collected from the steel plate. The softened portion of the surface of the steel plate (each surface is about 10% of the plate thickness, and each surface of the steel plate is about 10% when both sides of the steel plate are softened) is removed by grinding. When the thickness of the steel plate after removing the surface portion is more than 2.5 and less than 5 mm, two steel plates are overlapped and bolted together, and this is used as the thickness of the test piece. When the thickness of the steel plate is less than 2.5 mm, three steel plates are overlapped and bolted together, and this is used as the thickness of the test piece. The length direction of the test piece is the plate width direction, and the notch is set in a manner that the fracture propagates along the rolling direction. Based on the V-notch test piece, a Charpy impact test is performed at room temperature (about 25°C) in accordance with the provisions of JIS Z2242:2018. Next, the fracture of the test piece after the Charpy impact test was observed, and the ratio of the brittle fracture area to the total fracture area was calculated using image analysis software to determine the ratio of macroscopic brittle fractures in the Charpy impact test at room temperature.
[0209] [P segregation amount at the prior austenite grain boundary from 1 / 8 position to 1 / 2 position of the plate thickness: 3.5 atomic % or less]
[0210] P is an element that promotes grain boundary embrittlement by segregating to the original austenite grain boundaries, and is therefore a very important element in controlling the proportion of the above-mentioned macroscopic brittle fracture. This time, the inventors found that by reducing the P segregation amount in the original austenite grain boundaries from the 1 / 8 position to the 1 / 2 position of the plate thickness of the steel plate to less than 3.5 atomic %, the proportion of the above-mentioned macroscopic brittle fracture can be effectively controlled to less than 35.0%, and as a result, the hydrogen embrittlement resistance of the steel plate can be significantly improved. From the viewpoint of improving the hydrogen embrittlement resistance, the lower the P segregation amount in the above-mentioned original austenite grain boundaries, the better, for example, it can also be less than 3.2 atomic %, less than 3.0 atomic %, less than 2.5 atomic % or less than 2.0 atomic %. On the other hand, the lower limit is not particularly limited, and is ideally 0 atomic %. However, it is difficult to reduce the P content of the steel sheet to 0 mass % or to a level close to this level in terms of manufacturing cost, and it is also difficult to reduce the P segregation amount at the prior austenite grain boundary from the 1 / 8 position to the 1 / 2 position of the plate thickness of the steel sheet to 0 atomic %. Therefore, the P segregation amount may be, for example, 0.1 atomic % or more, 0.2 atomic % or more, 0.3 atomic % or more, 0.5 atomic % or more, or 1.0 atomic % or more.
[0211] [Measurement of P segregation amount]
[0212] In the present invention, the amount of P segregation in the prior austenite grain boundary from the 1 / 8 position to the 1 / 2 position of the plate thickness of the steel plate can be determined in the following manner. First, a test piece is collected from a position more than 50 mm from the end face of the steel plate. At this time, the front and back sides of the test piece are finished by mechanical grinding. In addition, when there is a coating layer (such as a plating layer) on the surface of the steel plate, the coating layer is removed, and the front and back sides of the test piece of the steel plate are finished by mechanical grinding. At this time, as long as the plate thickness from the 1 / 8 position to the 1 / 2 position can be measured, the plate thickness is not specifically specified, and the front and back sides of the test piece can also be removed by mechanical grinding in the same amount on each side in such a way that the plate thickness becomes 1.2 mm. A test piece with a length of 20 mm and a width of 3.2 mm is processed, and a V-shaped cut with an angle of 45° is inserted at a position with a length of 11.5 mm. The test piece is immersed in a 20%-ammonium thiocyanate solution. At this time, the immersion time is not particularly limited, as long as it is fixed in the Auger electron emission spectrometer when the original austenite grain boundary is exposed, for example, it can also be set to 48 hours. After the immersion is completed, the surface and back of the test piece are galvanized within 10 minutes. After plating, the test piece is quickly transferred to the Auger electron emission spectrometer for fracture. At this time, the time from plating to the fracture of the test piece is preferably set to within 1.5 hours, and more preferably set to within 0.5 hours. The test piece is fixed in the Auger electron emission spectrometer, and the cut part of the test piece is broken to expose the original austenite grain boundary. At this time, the device can be a field emission Auger electron spectrometer, and the model is not particularly limited. PHI680 manufactured by ULVAC-PHI can also be used. As the measurement conditions, the acceleration voltage can also be set to 10keV and the irradiation current can be set to 10nA. The exposed original austenite grain boundary is irradiated with electron beams at an acceleration voltage of 1 to 30kV to determine the atomic % of P in the grain boundary. The measurement is performed at 10 prior austenite grain boundaries from the position 1 / 8 of the plate thickness to the position 1 / 2 of the plate thickness from the surface. In order to prevent grain boundary contamination, it is preferred to complete the measurement quickly after fracture, and the measurement can also be completed within 30 minutes. The average value of the atomic % of P obtained is calculated and determined as the P segregation amount of the prior austenite grain boundaries from the position 1 / 8 of the plate thickness to the position 1 / 2 of the plate thickness of the steel plate.
[0213] [Plate thickness]
[0214] The steel plate according to the embodiment of the present invention generally has a plate thickness of 0.6 to 6.0 mm. Although not particularly limited, the plate thickness may be 1.0 mm or more, 1.2 mm or more, or 1.4 mm or more, and / or 5.0 mm or less, 4.0 mm or less, 3.0 mm or less, or 2.5 mm or less.
[0215] [Coating layer]
[0216] The steel sheet involved in the embodiment of the present invention may also further include a coating layer such as a plating layer on at least one surface, preferably on both surfaces, for the purpose of improving corrosion resistance, etc. Although not particularly limited, the coating layer, for example, contains at least one selected from zinc, aluminum, magnesium and their alloys. More specifically, the coating layer may also be a hot-dip coating layer or an electroplating layer. The hot-dip coating layer includes, for example, a hot-dip galvanized layer, an alloyed hot-dip galvanized layer, a hot-dip aluminum coating layer, a hot-dip Zn-Al alloy coating layer, a hot-dip Zn-Al-Mg alloy coating layer, a hot-dip Zn-Al-Mg-Si alloy coating layer, etc. The electroplating layer includes, for example, an electroplated zinc layer, an electroplated Zn-Ni alloy layer, etc. The coating layer is preferably a hot-dip galvanized layer, an alloyed hot-dip galvanized layer or an electroplated zinc layer. There is no particular limitation on the amount of coating layer attached, and it may be a general amount of attachment.
[0217] [Mechanical properties]
[0218] The steel plate involved in the embodiment of the present invention has a tensile strength of 1500MPa or more. The tensile strength is preferably 1600MPa or more, 1700MPa or more, or 1800MPa or more. According to the steel plate involved in the embodiment of the present invention, although it has such a very high tensile strength, the hydrogen embrittlement resistance of the bent portion can be significantly improved by the combination of the appropriate control of the ratio of the macroscopic brittle fracture described above and the prescribed softening in the surface layer of the steel plate. The upper limit of the tensile strength is not particularly limited, for example, the tensile strength can also be 2300MPa or less, 2200MPa or less, or 2100MPa or less. In addition, according to the steel plate involved in the embodiment of the present invention, excellent bending workability can be achieved, more specifically, a total elongation of 4.0% or more can be achieved. The total elongation is preferably 5.0% or more, more preferably 6.0% or more or 7.0% or more. The upper limit is not particularly limited, for example, the total elongation can also be 12.0% or less or 10.0% or less. The tensile strength and the total elongation can be measured by conducting a tensile test in accordance with JIS Z 2241:2011 using a JIS No. 5 test piece collected in a direction parallel to the rolling direction of the steel sheet in the longitudinal direction of the test piece.
[0219] As described above, the steel sheet according to the embodiment of the present invention has a very high tensile strength of 1500 MPa or more, but it is excellent in hydrogen embrittlement resistance and bending workability. Therefore, it is very useful for use as, for example, automotive frame members and bumpers, and other structural parts and reinforcements requiring strength. It is also very suitable for uses requiring high bending workability in addition to high strength.
[0220] <Method for manufacturing steel sheet>
[0221] Next, a preferred method for manufacturing a steel sheet according to an embodiment of the present invention will be described. The following description is intended to exemplify a characteristic method for manufacturing a steel sheet according to an embodiment of the present invention, and is not intended to limit the steel sheet to be manufactured by the manufacturing method described below.
[0222] The method for manufacturing a steel plate according to an embodiment of the present invention is characterized by including the following steps:
[0223] A hot rolling process, which includes heating a slab associated with a steel plate and having the chemical composition described above to a temperature of 1100 to 1300° C., then performing finish rolling, cooling the finish rolled steel plate to a temperature below 500° C. at an average cooling rate of 20° C. / s or more, and then performing coiling, wherein the finishing temperature of the finish rolling is 850 to 1050° C.;
[0224] A pickling step, in which the obtained hot-rolled steel sheet is pickled;
[0225] A cold rolling process, in which the pickled hot-rolled steel sheet is cold rolled at a reduction rate of 35 to 80%;
[0226] an annealing step, which is a step of annealing the obtained cold-rolled steel sheet, the annealing comprising the steps of heating the cold-rolled steel sheet to a temperature of 700° C. or higher in an atmosphere having a dew point of −30.0° C. to 10.0° C. and a hydrogen concentration of 1.0% to 10.0%, then maintaining the cold-rolled steel sheet at a maximum heating temperature of 830° C. to 900° C. for 20 to 150 seconds, and then limiting the residence time in the temperature range of 400° C. to 600° C. to 2 to 350 seconds; and
[0227] The cooling step is to cool the cold-rolled steel sheet to room temperature at an average cooling rate of 20° C. / sec or more.
[0228] Hereinafter, each step will be described in detail.
[0229] [Hot rolling process]
[0230] [Heating of slab]
[0231] First, a slab associated with a steel plate and having the chemical composition described above is heated. The slab used is preferably cast by a continuous casting method from the viewpoint of productivity, but can also be manufactured by an ingot casting method or a thin slab casting method. The slab used may also contain a large amount of alloying elements in order to obtain a high-strength steel plate. Therefore, it is necessary to dissolve the alloying elements in the slab by heating before the slab is transferred to hot rolling. If the heating temperature is lower than 1100°C, the alloying elements cannot be fully dissolved in the slab and coarse alloy carbides remain, sometimes causing brittle cracks during hot rolling. Therefore, the heating temperature is preferably above 1100°C. There is no particular limit on the upper limit of the heating temperature, but from the viewpoint of the capacity of the heating equipment and productivity, it is preferably below 1300°C.
[0232] [Rough rolling]
[0233] In this method, for example, the heated slab may be subjected to rough rolling before finish rolling in order to adjust the sheet thickness, etc. The conditions of the rough rolling are not particularly limited as long as a desired sheet bar size can be secured.
[0234] [Finish rolling]
[0235] Next, the heated slab or the slab that has been rough-rolled as required is subjected to finish rolling. Since the slab used as described above contains a large amount of alloying elements, it is necessary to increase the rolling load during hot rolling. Therefore, it is preferred that hot rolling be performed at a high temperature. In particular, the finish rolling end temperature is important in controlling the metal structure of the steel plate. If the finish rolling end temperature is low, the metal structure becomes uneven and sometimes the formability is reduced. Therefore, the finish rolling end temperature is preferably above 850°C. On the other hand, in order to suppress the coarsening of austenite, it is preferred that the finish rolling end temperature is below 1050°C.
[0236] [Cooling-Coiling]
[0237] Next, the finish rolled steel sheet is cooled to 500°C or less at an average cooling rate of 20°C / sec or more and then coiled. If the average cooling rate is lower than 20°C / sec or the coiling temperature exceeds 500°C, P segregation occurs during the hot rolling process, making the hot rolled steel sheet brittle, and sometimes making subsequent cold rolling difficult. For example, the average cooling rate is preferably 25°C / sec or more, and the coiling temperature is preferably 480°C or less.
[0238] [Pickling process]
[0239] Next, the obtained hot-rolled steel sheet is pickled to remove the oxide scale formed on the surface of the hot-rolled steel sheet. The pickling can be performed under conditions suitable for removing the oxide scale, and can be performed once or in multiple times to ensure the removal of the oxide scale.
[0240] [Cold rolling process]
[0241] The pickled hot-rolled steel sheet is cold rolled at a reduction ratio of 35 to 80% in the cold rolling process. By setting the reduction ratio of cold rolling to 35% or more, the shape of the cold-rolled steel sheet can be maintained flat, and the decrease in ductility in the final product can be suppressed. The reduction ratio of cold rolling is preferably 50% or more. On the other hand, by setting the reduction ratio of cold rolling to 80% or less, it is possible to prevent the rolling load from becoming too large and making the rolling difficult. The reduction ratio of cold rolling is preferably 70% or less. There is no particular limitation on the number of rolling passes and the reduction ratio of each pass, as long as they are appropriately set in such a way that the reduction ratio of all cold rolling falls within the above range.
[0242] [Annealing process]
[0243] [Heating to a temperature of 700°C or higher in an atmosphere with a dew point of -30.0 to 10.0°C and a hydrogen concentration of 1.0 to 10.0%]
[0244] The obtained cold-rolled steel sheet is annealed by heating to a temperature of 700°C or higher in a heating furnace and a soaking furnace of a continuous annealing line, for example, in an atmosphere having a dew point of -30.0 to 10.0°C and a hydrogen concentration of 1.0 to 10.0% (for example, nitrogen as the balance). By annealing in such an atmosphere and under high temperature conditions, the surface layer of the steel sheet can be appropriately decarburized. As a result, by controlling the average carbon concentration Cs in the final steel plate from at least one surface, especially from both surfaces to 10% of the plate thickness, within the range of 0.10 to 0.90 times (0.10≤Cs / Cc≤0.90) the average carbon concentration Cc of the base material, the desired softening of the surface layer of the steel plate can be achieved, that is, the average Vickers hardness Hs in the area from at least one surface of the steel plate, especially from both surfaces to 10% of the plate thickness can be made less than 0.95 times the average Vickers hardness Hc at 1 / 2 of the plate thickness (Hs / Hc≤0.95). If the dew point is lower than -30.0°C, or the hydrogen concentration exceeds 10.0% and / or the heating temperature is lower than 700°C, the surface layer cannot be fully decarburized. Therefore, even if the subsequent steps are properly implemented, 0.10≤Cs / Cc≤0.90 cannot be achieved in the final steel plate, and the desired surface softening, i.e., Hs / Hc≤0.95, cannot be achieved. On the other hand, if the dew point exceeds 10.0°C and / or the hydrogen concentration is lower than 1.0%, decarburization is excessively performed due to the difference in C content, and the desired tensile strength of 1500 MPa or more cannot be achieved in the final steel plate. From the viewpoint of desired surface softening and ensuring strength, it is preferred that the dew point is -20.0 to 8.0°C, the hydrogen concentration is 1.5 to 10.0%, and the heating temperature is 750°C or higher.
[0245] For example, only the surface layer of one side of the steel plate may be set to Hs / Hc≤0.95. As a specific method for achieving this purpose, for example, by overlapping two cold-rolled steel plates during the annealing process and performing annealing under the conditions described above, only the surface layer of one side of the steel plate may be decarburized and softened.
[0246] [Maintain at a maximum heating temperature of 830 to 900°C for 20 to 150 seconds]
[0247] Next, the cold-rolled steel sheet is further heated to a maximum heating temperature of 830 to 900°C in an atmosphere of the previously recorded dew point and hydrogen concentration, and is maintained at the maximum heating temperature for 20 to 150 seconds. Thus, by promoting austenitization, the desired hard structure composed of martensite and the like is obtained in the subsequent cooling process, so that a tensile strength of more than 1500 MPa can be achieved reliably. In addition, within such a temperature range, the diffusion of P is relatively fast due to the high temperature, and the segregation of P to the original austenite grain boundary in the final steel sheet can be suppressed or reduced. As a result, the amount of P segregation in the original austenite grain boundary from the 1 / 8 position of the plate thickness to the 1 / 2 position of the plate thickness of the steel sheet can be controlled to less than 3.5 atomic %, and the proportion of macroscopic brittle fracture in the Charpy impact test at room temperature can be made less than 35.0%. Furthermore, by maintaining the temperature within the above range for 20 to 150 seconds, the surface layer of the steel sheet can be sufficiently decarburized, so that the desired surface softening of the steel sheet with Hs / Hc being 0.95 or less can be achieved.
[0248] If the maximum heating temperature is lower than 830°C, austenitization is insufficient, and hard structures such as martensite cannot be fully obtained in the final steel plate, and a tensile strength of more than 1500MPa cannot be achieved. In addition, because the diffusion of P becomes relatively slow, the grain boundary segregation of P in the final structure cannot be fully suppressed. In this case, the proportion of the above-mentioned macroscopic brittle fracture cannot be controlled below 35.0%. On the other hand, if the maximum heating temperature exceeds 900°C, the martensite coarsens in the final structure, and even if the amount of P segregation as a whole is the same due to the decrease in the grain boundary area, the amount of P segregation at the original austenite grain boundary is relatively increased. As a result, the proportion of the above-mentioned macroscopic brittle fracture cannot be controlled below 35.0%. The preferred maximum heating temperature is 835-896°C.
[0249] In addition, if the holding time at the maximum heating temperature is less than 20 seconds, austenitization is insufficient, and hard structures such as martensite cannot be fully obtained in the final structure, and the tensile strength of more than 1500 MPa cannot be achieved. In addition, since the surface part of the steel plate cannot be fully decarburized, the desired surface softening of Hs / Hc below 0.95 cannot be achieved. On the other hand, if the holding time at the maximum heating temperature exceeds 150 seconds, even in the range of 830 to 900°C, the segregation of P to the grain boundary sometimes increases due to the long time. In this case, the proportion of the above-mentioned macroscopic brittle fracture cannot be controlled below 35.0%. In addition, by extending the holding time at high temperature and excessively decarburizing, the desired tensile strength of more than 1500 MPa cannot be achieved in the final steel plate. The preferred holding time is 23 to 146 seconds.
[0250] [Residence time in the temperature range of 400 to 600°C: 2 to 350 seconds]
[0251] Next, it is important to limit the residence time of the cold-rolled steel sheet in the temperature range of 400 to 600°C before the cooling process to 2 to 350 seconds. When the temperature is relatively high, the diffusion of P becomes dominant, so the segregation of P to the grain boundary can be suppressed or reduced. However, in the relatively low temperature range of 400 to 600°C, the diffusion of P slows down, making it easy for P to segregate at the grain boundaries. Therefore, in order to suppress or reduce the grain boundary segregation of P, it is necessary to limit the residence time of the cold-rolled steel sheet in the temperature range of 400 to 600°C to a prescribed range. Specifically, it is important to limit the residence time to less than 350 seconds. In this way, the P segregation amount at the original austenite grain boundary from the 1 / 8 position of the plate thickness to the 1 / 2 position of the plate thickness of the steel plate can be reliably controlled to be less than 3.5 atomic %, and the proportion of macroscopic brittle fractures in the Charpy impact test at room temperature can be made less than 35.0%. If the residence time in the temperature range of 400 to 600°C exceeds 350 seconds, the segregation of P in the original austenite grain boundaries of the final structure becomes particularly significant, and the ratio of the above-mentioned macroscopic brittle fracture cannot be controlled below 35.0%. In order to effectively suppress the grain boundary segregation of P, the preferred residence time is 300 seconds or less. Although from the viewpoint of suppressing the grain boundary segregation of P, the shorter the residence time, the better, but it is actually impossible to reduce it to near 0 seconds, so the lower limit of the residence time is set to 2 seconds.
[0252] [Cool to room temperature at an average cooling rate of 20°C / sec or more]
[0253] Finally, the cold-rolled steel sheet after the annealing process is cooled to room temperature at an average cooling rate of 20°C / sec or more in the subsequent cooling process. By making the final structure a hard structure mainly composed of martensite, a tensile strength of 1500MPa or more can be achieved. On the other hand, if the average cooling rate is lower than 20°C / sec, more bainite is formed during the cooling process, and sufficient tensile strength cannot be achieved.
[0254] [Coating process]
[0255] The surface of the cold-rolled steel sheet may also be subjected to a coating treatment for the purpose of improving corrosion resistance, etc. The coating treatment may also be a treatment such as hot-dip plating, alloyed hot-dip plating, or electroplating. For example, as a coating treatment, the steel sheet may be subjected to a hot-dip galvanizing treatment, or an alloying treatment may be performed after the hot-dip galvanizing treatment. The coating layer, for example, contains at least one selected from zinc, aluminum, magnesium, and their alloys. More specifically, the coating layer may also be a hot-dip plating layer or an electroplating layer. The hot-dip plating layer, for example, includes a hot-dip galvanizing (GI) layer, an alloyed hot-dip galvanizing (GA) layer, a hot-dip aluminum plating layer, a hot-dip Zn-Al alloy layer, a hot-dip Zn-Al-Mg alloy layer, a hot-dip Zn-Al-Mg-Si alloy layer, etc. The electroplating layer, for example, includes an electroplated zinc layer, an electroplated Zn-Ni alloy layer, etc. The preferred coating layer is a hot-dip galvanizing layer, an alloyed hot-dip galvanizing layer, or an electroplated zinc layer. The specific conditions of the coating treatment and the alloying treatment are not particularly limited, and any appropriate conditions known to those skilled in the art are preferred.
[0256] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples at all.
[0257] Example
[0258] In the following examples, steel sheets according to the embodiments of the present invention were produced under various conditions, and the tensile strength, total elongation, and hydrogen embrittlement resistance of the obtained steel sheets were investigated.
[0259] [Example A]
[0260] First, molten steel was cast by continuous casting to form slabs having various chemical compositions shown in Table 1, and these slabs were heated to 1230°C and hot rolled. Hot rolling was performed by performing rough rolling and finish rolling, and the finishing temperature of the finish rolling was 940°C. Then, the finish-rolled steel sheet was cooled to 420°C at an average cooling rate of 30°C / second, and then coiled. Then, the obtained hot-rolled steel sheet having a plate thickness of 2.6 mm was pickled, and then cold-rolled at a reduction ratio of 45% to obtain a cold-rolled steel sheet having a plate thickness of 1.4 mm. Then, the obtained cold-rolled steel sheet was heated to a temperature of 700°C or more in an atmosphere with a dew point of -2.0°C and 6.0% hydrogen (nitrogen as the balance), and the surface layer parts on both sides of the steel sheet were fully decarburized by maintaining the maximum heating temperature of 860°C for 90 seconds, and then the retention time in the temperature range of 400 to 600°C was adjusted to reach 180 seconds. Finally, the cold-rolled steel sheet is cooled to room temperature at an average cooling rate of 30° C. / sec, and then hot-dip galvanizing (GI) or alloyed hot-dip galvanizing (GA) is preferably performed as a coating treatment.
[0261] The properties of the obtained steel sheets were measured and evaluated by the following methods.
[0262] [Tensile strength (TS) and total elongation (t-El)]
[0263] The tensile strength (TS) and total elongation (t-El) were measured by performing a tensile test in accordance with JIS Z 2241:2011 using a JIS No. 5 test piece collected in a direction parallel to the rolling direction of the steel sheet in the longitudinal direction of the test piece.
[0264] [Evaluation of hydrogen embrittlement resistance]
[0265] The hydrogen embrittlement resistance in the bent portion of the obtained steel plate was evaluated by the following method. Specifically, first, the steel plate was sheared with a clearance of 12.5%, and then a U-bend test was performed at 8R. Next, a strain gauge was bonded to the center of the obtained test piece, and stress was applied by tightening the two ends of the test piece with bolts. The applied stress is calculated from the deformation of the monitored strain gauge. The load stress applies a stress corresponding to 80% of the tensile strength (TS). This is because it can be considered that the residual stress introduced during forming corresponds to the tensile strength of the steel plate. The obtained U-bend test piece was immersed in an aqueous HCl solution with a liquid temperature of 35°C and a pH of 2, and then kept for 72 hours to investigate the presence or absence of cracks. Since the lower the pH of the HCl aqueous solution and the longer the immersion time, the greater the amount of hydrogen intruding into the steel plate, the hydrogen embrittlement environment is a harsh condition. After immersion, the case where a crack longer than 1 mm was visible in the U-bend test piece was evaluated as unqualified (NG), and the case where no crack longer than 1 mm was visible in the U-bend test piece (i.e., there was no crack or even if there was a crack, the crack was less than 1 mm) was evaluated as qualified (OK).
[0266] The steel plates with a tensile strength (TS) of 1500 MPa or more and an OK hydrogen embrittlement resistance are evaluated as high-strength steel plates with excellent hydrogen embrittlement resistance in the bent portion. The results are shown in Table 2. In Table 2 and Table 4 shown later, the values of Hs / Hc and Cs / Cc only represent the values calculated based on the average Vickers hardness Hs and the average carbon concentration Cs in the area from the surface of one side of the steel plate to 10% of the plate thickness. However, since all steel plates are manufactured by performing the same treatment on both sides thereof, the values of Hs and Cs are substantially the same on both sides of the steel plate. In fact, it was confirmed in several steel plates that these values are also the same on both sides of the steel plate. In addition, in Table 2 and Table 4 shown later, the remaining structure is bainite, pearlite and / or retained austenite.
[0267] Table 1-1
[0268]
[0269] Underlined bold words indicate that they are outside the scope of the present invention.
[0270] Table 1-2
[0271]
[0272] Underlined bold words indicate that they are outside the scope of the present invention.
[0273] Table 2
[0274]
[0275] Underlined bold words indicate that they are outside the scope of the present invention.
[0276] Referring to Tables 1 and 2, it can be seen that Example X-1 has a TS of less than 1500 MPa due to the low C content. Example Y-1 has a high C content, which forms coarse grain boundary carbides and reduces the hydrogen embrittlement resistance of the bent portion. Example Z-1 has a high Si content, which reduces the hydrogen embrittlement resistance of the bent portion. Example AA-1 has a low Mn content, which reduces the hardenability and fails to obtain the desired hard structure, resulting in a TS of less than 1500 MPa. Example AB-1 has a high Mn content, which reduces the hydrogen embrittlement resistance of the bent portion. Example AC-1 has a high P content, which fails to control the ratio of macroscopic brittle fractures to less than 35.0%, resulting in reduced hydrogen embrittlement resistance of the bent portion. Although Examples AD-1 to AT-1 have good TS, they cannot achieve sufficient hydrogen embrittlement resistance of the bent portion due to the high contents of S, Al, N, O, Co, Ni, Mo, Cr, Ti, B, Cu, W, Sn, Sb, Ca, Y and Zr in each example.
[0277] In contrast, in the steel plates involved in all the invention examples, by having a prescribed chemical composition, controlling Hs / Hc to less than 0.95, and controlling the proportion of macroscopic brittle fractures in the Charpy impact test to less than 35.0%, the hydrogen embrittlement resistance of the bent portion can be significantly improved despite having a very high TS of more than 1500 MPa.
[0278] [Example B]
[0279] Next, in order to investigate the influence of the manufacturing conditions, steel types A to W showing excellent properties in Table 2 were used as the target, and steel plates having a plate thickness of 1.4 mm were manufactured under the manufacturing conditions shown in Table 3. The conditions other than the manufacturing conditions shown in Table 3 were the same as those in Example A, and the properties of the obtained steel plates were measured and evaluated in the same manner as in Example A. The results are shown in Table 4.
[0280] Table 3
[0281]
[0282] Underlined boldface words indicate departures from the preferred range.
[0283] Table 4
[0284]
[0285] Underlined bold words indicate that they are outside the scope of the present invention.
[0286] Referring to Tables 3 and 4, it can be seen that Example H-3 cannot fully decarburize the surface layer due to the low dew point in the annealing process, and cannot achieve the desired surface softening, that is, Hs / Hc≤0.95. As a result, the hydrogen embrittlement resistance of the bent portion is reduced. Example J-3 cannot achieve a TS of more than 1500MPa due to the low hydrogen concentration in the annealing process, and the surface layer is decarburized excessively. Example K-3 cannot fully decarburize the surface layer due to the high hydrogen concentration in the annealing process, and cannot achieve Hs / Hc≤0.95. As a result, the hydrogen embrittlement resistance of the bent portion is reduced. Example L-3 cannot achieve sufficient austenitization due to the low maximum heating temperature in the annealing process, and the desired hard structure cannot be obtained in the final steel plate. As a result, a TS of more than 1500MPa cannot be achieved. In Example M-3, the martensite in the final structure is coarsened due to the high maximum heating temperature in the annealing process. It is believed that the P segregation amount in the original austenite grain boundary is relatively increased due to the decrease in the grain boundary area associated with it. As a result, the proportion of macroscopic brittle fractures cannot be controlled below 35.0%, and the hydrogen embrittlement resistance of the bent portion is reduced. In Example N-3, the austenitization is insufficient due to the short holding time at the maximum heating temperature in the annealing process, and the desired hard structure cannot be obtained in the final steel plate. As a result, TS of more than 1500MPa cannot be achieved. In Example O-3, the segregation of P to the grain boundary is increased due to the long holding time at the maximum heating temperature in the annealing process. As a result, the proportion of macroscopic brittle fractures cannot be controlled below 35.0%, and the hydrogen embrittlement resistance of the bent portion is reduced. In Example P-3, the segregation of P to the grain boundary is increased due to the long retention time in the temperature range of 400 to 600°C in the annealing process. As a result, the proportion of macroscopic brittle fractures cannot be controlled below 35.0%, and the hydrogen embrittlement resistance of the bent portion is reduced. Example Q-3 cannot obtain the desired hard structure in the final steel plate due to the low average cooling rate in the cooling process. As a result, TS above 1500MPa cannot be achieved. These comparative examples show that even if only one of "Hs / Hc≤0.95" and "the proportion of macroscopic brittle fractures: below 35.0%" is satisfied, sufficient hydrogen embrittlement resistance of the bent portion cannot be achieved.
[0287] In contrast, in all the examples of the present invention, by using a slab having a predetermined chemical composition, and in particular by appropriately controlling the dew point, hydrogen concentration, maximum heating temperature and holding time at the temperature, retention time in the temperature range of 400 to 600°C, and average cooling rate in the cooling process in the annealing process, it is possible to manufacture a steel sheet that satisfies the main conditions of "Hs / Hc ≤ 0.95" and "ratio of macroscopic brittle fracture: 35.0% or less". As a result, despite having a very high tensile strength of 1500 MPa or more, the hydrogen embrittlement resistance of the bent portion can be significantly improved. Although the dew point of Example I-3 in the annealing process is high, the surface layer portion does not become excessively decarburized due to the relatively high original C content, and a TS of 1500 MPa or more can be achieved in the final steel sheet.
Claims
1. A steel plate, characterized in that: The chemical composition is C: 0.15-0.40% by mass, Si: 0.01-2.00%, Mn: 0.80~3.50%, P:0.0001~0.0200%、 S:0.0001~0.0200%、 Al:0.001~1.000%、 N:0.0001~0.020%、 O:0.0001~0.0200%、 Co: 0~0.5000%, Ni: 0~1.000%, Mo: 0~1.000%, Cr:0~2.000%、 Ti: 0~0.500%, B:0~0.0100%、 Nb: 0~0.500%, V:0~0.500%、 Cu: 0~0.500%, W:0~0.100%、 Ta: 0~0.100%、 Sn: 0~0.100%, Sb: 0~0.100%, As: 0~0.100%, Mg: 0~0.0500%, Ca: 0~0.050%, Y:0~0.050%、 Zr:0~0.050%、 La: 0~0.050%, Ce: 0 to 0.050%, and The rest: Fe and impurities. The average Vickers hardness Hs in the region from at least one surface to 10% of the plate thickness is 0.95 times or less of the average Vickers hardness Hc at a position 1 / 2 of the plate thickness, The ratio of macroscopic brittle fractures in a Charpy impact test at room temperature is 35.0% or less, and the tensile strength is 1500 MPa or more.
2. The steel plate according to claim 1, characterized in that: The chemical composition contains, by mass%, one or more elements selected from the following: Co: 0.0100~0.5000%, Ni: 0.010~1.000%, Mo: 0.010~1.000%, Cr:0.001~2.000%、 Ti: 0.001~0.500%, B:0.0001~0.0100%、 Nb: 0.001~0.500%, V:0.001~0.500%、 Cu: 0.001~0.500%, W:0.001~0.100%、 Ta: 0.001~0.100%, Sn: 0.001~0.100%, Sb: 0.001~0.100%, As: 0.001~0.100%, Mg: 0.0001~0.0500%, Ca: 0.001~0.050%, Y:0.001~0.050%、 Zr:0.001~0.050%、 La: 0.001 to 0.050%, and Ce: 0.001~0.050%.
3. The steel plate according to claim 1 or 2, characterized in that: The microstructure at the half thickness position contains, by area ratio: Martensite and tempered martensite: more than 93.0% in total, and Ferrite: less than 7.0%.
4. The steel plate according to claim 1 or 2, characterized in that: The average carbon concentration Cs in the region from at least one surface to 10% of the plate thickness is 0.10 to 0.90 times the average carbon concentration Cc of the base material.
5. The steel plate according to claim 1 or 2, characterized in that: The amount of P segregation in the prior austenite grain boundaries from the 1 / 8 position to the 1 / 2 position of the plate thickness is 3.50 atomic % or less.
6. The steel plate according to claim 1 or 2, characterized in that: The invention further comprises a coating layer on at least one surface, wherein the coating layer contains at least one selected from zinc, aluminum, magnesium and alloys thereof.
Citation Information
Patent Citations
Ultrahigh strength cold rolled steel sheet and its production
JP1998130782A
Super-high strength cold-rolled steel sheet having excellent bending properties
JP2011179030A
High-strength hot-dip galvanized steel sheet and method for manufacturing same
WO2020136988A1
High-strength hot-dip zinc-coated steel sheet and method for manufacturing same
WO2020136990A1